Epidemiological Study of the Brucellosis in Iran, Andimeshk, 2001-2016 - Mansour Kashfi; Nahid Hatamian; Tayebeh Rakhshani (Shiraz University of Medical Sciences, 2018)
Introduction: Despite the provision of health care in Iran, brucellosis is still an endemic disease, so this study was carried out to determine the epidemiology of brucellosis in Andimeshk city during 2001-2016. Materials and Methods: This cross-sectional study was conducted on patients with brucellosis, which were reported by governmental and non-governmental departments and received relevant diagnostic and laboratory information after receiving reports from patients. The obtained information was entered in the survey form. Sampling was done by census. SPSS version 20 was applied for analysis of data using descriptive statistics as well as the chi-square and independent t-test; a significant level of 0.05 was considered. Results: In the study period, there were 713 patients with brucellosis in Andimeshk. There were 390 males and 324 females with a male to female ratio of 1.02:1. The age of the patients ranged from 1 to 74 years with a mean of 31.19±17.03 years. The annual incidence rate per 100,000 persons was 24.42. There was a statistically significant association (p<0.05) between sex and exposure to infected milk and cattle. Also, the results showed that there was no statistically significant association (p>0.05) between the infected milk and job, year, season and month. Conclusion: In conclusion, the findings of this study showed that the incidence of brucellosis was higher among males, young people, and dairy farmers. Therefore, continuous surveillance and efforts are required to further decrease the cases of brucellosis.